Impact of motor size &efficiency on acceleration, Fuel consumption &Emissions of split- axle through- the- road parallel hybrid electric vehicle - Zulkifli, S.A. (Trans Tech Publications Ltd, 2014)
A split-axle parallel hybrid drive-train with in-wheel motors allows for existing combustion-engine-driven vehicles to be converted into a hybrid vehicle with minor mechanical modification, resulting in a retrofit-conversion hybrid electric vehicle (HEV). This is achieved by placing electric motors in the hub of the otherwise non-driven wheels. Due to the wheel hubâs size constraint, the allowable size and power of the electric in-wheel motor that can be installed is severely restricted to less than 10 kW per wheel, which raises the concern of lack of improved performance compared to the original vehicle. This work analyzes the influence of motor sizing and efficiency on acceleration performance, fuel consumption and emission levels of three different converted hybrid vehicles, through simulation. Results provide insight into sensitivity of different-sized vehicles with varying-size engines, to the size and efficiency of the retrofitted electric motor. Â© (2014) Trans Tech Publications, Switzerland. All Rights Reserved.